Studi Literatur: Identifikasi Akar Masalah Duplikasi Data Rekam Medis Berbasis Solusi Continuous Improvement - Afrodita Putri Alesca; Sinta Novratilova; Aulia Rahmawati; Dian Nur Afifah; Clara Indah Ayu Meilan; Adi Reza Saputra; Muhammad Junaid Farrukh (Jurnal Persada Husada Indonesia, 2026)
Research Objective: This study aimed to identify the root causes of medical record-number duplication and synthesize evidence-informed continuous-improvement recommendations. Methodology: A Systematic Literature Review (SLR) was conducted in Google Scholar in June 2026 using combinations of “medical record duplication,” “Electronic Medical Records (EMR),” and “continuous improvement.” Articles published between 2022 and 2026 were screened using predefined eligibility criteria. Of 7,580 records identified, 11 articles were included and analyzed through qualitative thematic coding and narrative quality appraisal. Results: The evidence was grouped into five interrelated dimensions: human resources, systems and technology, processes and Standard Operating Procedures (SOPs), policies and governance, and infrastructure. Human-resource factors were the most frequently reported, while system limitations, weak identity-verification procedures, limited governance, and infrastructure disruptions also contributed to assigning more than one medical record number to the same patient. The findings were mapped to PDCA, Kaizen, data cleansing, and Master Patient Index (MPI) strategies. Conclusion: Medical record-number duplication is a multidimensional patient-safety and data-quality problem. The proposed continuous-improvement framework should be interpreted as an evidence-informed synthesis that may help healthcare facilities reduce new duplication and strengthen patient-identity management; its effectiveness requires local implementation and evaluation.